Differential Colonization and Succession of Microbial Communities in Rock and Soil Substrates on a Maritime Antarctic Glacier Forefield - Garrido-Benavent, Isaac; Pérez-Ortega, Sergio; Durán, Jorge; Ascaso, Carmen; Pointing, Stephen B.; Rodríguez-Cielos, Ricardo; Navarro, Francisco; de los Ríos, Asunción (Frontiers in Microbiology, 2020)
Glacier forefields provide a unique chronosequence to assess microbial or plant colonization and ecological succession on previously uncolonized substrates. Patterns of microbial succession in soils of alpine and subpolar glacier forefields are well documented but those affecting high polar systems, including moraine rocks, remain largely unexplored. In this study, we examine succession patterns in pioneering bacterial, fungal and algal communities developing on moraine rocks and soil at the Hurd Glacier forefield (Livingston Island, Antarctica). Over time, changes were produced in the microbial community structure of rocks and soils (ice-free for different lengths of time), which differed between both substrates across the entire chronosequence, especially for bacteria and fungi. In addition, fungal and bacterial communities showed more compositional consistency in soils than rocks, suggesting community assembly in each niche could be controlled by processes operating at different temporal and spatial scales. Microscopy revealed a patchy distribution of epilithic and endolithic lithobionts, and increasing endolithic colonization and microbial community complexity along the chronosequence. We conclude that, within relatively short time intervals, primary succession processes at polar latitudes involve significant and distinct changes in edaphic and lithic microbial communities associated with soil development and cryptogamic colonization.